2009
DOI: 10.1094/phyto-99-3-0243
|View full text |Cite
|
Sign up to set email alerts
|

ThePi40Gene for Durable Resistance to Rice Blast and Molecular Analysis ofPi40-Advanced Backcross Breeding Lines

Abstract: Rice blast severely reduces production in both irrigated and water-stressed upland ecosystems of tropical and temperate countries. Nearly 50 blast resistance genes have been identified and some of those are incorporated into several rice cultivars. However, most of the resistance genes break down in a few years because of their race specificity and the rapid change in pathogenicity of the blast fungus (Magnaporthe grisea). The objective of this study was to analyze advanced backcross breeding lines (ABL) posse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 25 publications
1
42
0
3
Order By: Relevance
“…Using other foreground markers none of plants were found as heterozygous condition which indicates that some blast resistant gene disappeared due to the backcrossed with MR219. This statement is more coincide with the findings of Suh et al (2009) who found that some genes were lost during the recombination process in segregating generations of advanced backcross lines. The two polymorphic (RM6836 -238bp and RM8225 -212bp) linked markers were used to evaluate BC 2 F 1 progenies.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Using other foreground markers none of plants were found as heterozygous condition which indicates that some blast resistant gene disappeared due to the backcrossed with MR219. This statement is more coincide with the findings of Suh et al (2009) who found that some genes were lost during the recombination process in segregating generations of advanced backcross lines. The two polymorphic (RM6836 -238bp and RM8225 -212bp) linked markers were used to evaluate BC 2 F 1 progenies.…”
Section: Resultssupporting
confidence: 90%
“…Rice blast caused by Magnaporthe oryzae (M. oryzae) is the most devastating diseases of rice worldwide (Khush & Jena, 2009;Liu et al, 2010). Rice blast severely reduces production in both irrigated and water stressed upland ecosystems of tropical and temperate countries (Suh et al, 2009). The incorporation of blast resistance genes into cultivars is the most preferential strategy in rice breeding program to prevent this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Many pathogenic races have been identified in M. grisea infecting rice, and this variability has been cited as the principal cause for the frequent breakdown of resistance in rice varieties (25). Although pathogenic variations in the M. grisea populations adapted to rice, wheat, foxtail millet, finger millet, pearl millet, and several weed hosts have been reported (12,13,21,26), there is no infor- Table 3 a Resistant = ≤10% head blast incidence, ≤3.0 score on a 1-to-9 scale, and ≤2.0 score on a 1-to-5 scale; moderately resistant = 11 to 30% head blast incidence, 3.1 to 5.0 score on a 1-to-9 scale, and 2.1 to 3.0 score on a 1-to-5 scale; susceptible = 31 to 50% head blast incidence, 5.1 to 7.0 score on a 1-to-9 scale, and 3.1 to 4.0 score on a 1-to-5 scale; and highly susceptible = >50% head blast incidence, >7.0 score on a 1-to-9 scale, and >4.0 score on a 1-to-5 scale.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA was extracted from the fresh frozen leaves of the rice cultivars by a modified CTAB method (Rogers and Bendich, 1988). The procedure used in the PCR assay was as described by Suh et al (2009). The PCR products were detected using 4% denaturing polyacrylamide gel electrophoresis with silver staining.…”
Section: Ssr Marker and Genetic Diversity Analysismentioning
confidence: 99%